2010
DOI: 10.4321/s1130-01082010000100006
|View full text |Cite
|
Sign up to set email alerts
|

H. pylori and mitochondrial changes in epithelial cells: The role of oxidative stress

Abstract: Infection with H. pylori plays a role in the pathogenesis of gastritis, peptic ulcer, gastric carcinoma, and gastric lymphoma, but mechanisms leading to the various clinical manifestations remain obscure and are the primary focus of research in this field. Proliferation and apoptosis are essential in the maintenance of gastric tissue homeostasis, and changes seen in their balance may condition gastric mucosal changes during infection. Thus, excessive apoptosis or proliferation inhibition will result in cell ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Increasing evidence has shown that bioenergetics and mitochondrial function are impaired in FMS [42–44] and PUD [4547] patients. Although it is unclear whether oxidative stress is a common pathway of PUD and FMS, recent studies have shown that oxidative stress can cause the pathophysiological mechanisms that culminate in the symptoms of PUD and FMS.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has shown that bioenergetics and mitochondrial function are impaired in FMS [42–44] and PUD [4547] patients. Although it is unclear whether oxidative stress is a common pathway of PUD and FMS, recent studies have shown that oxidative stress can cause the pathophysiological mechanisms that culminate in the symptoms of PUD and FMS.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, researchers have paid much attention to H. pylori. Researchers recently[46] found that pro- and anti-inflammatory cytokines and oxidative stress play important roles in the development of diseases such as peptic ulceration and gastric adenocarcinoma in patients with H. pylori infection. In contrast, another study regarding the effects of chronic excessive alcohol consumption on the liver and cardiovascular system has demonstrated that modest alcohol intake, such as 1–2 drinks (a standard drink is equivalent to 10 g of ethanol) per day, may decrease cardiovascular mortality[7].…”
Section: Introductionmentioning
confidence: 99%
“…In normal cells, there is a balance between apoptosis and proliferation, but in gastric disorders caused by H . pylori , this balance is altered 23 , 24 . This is of prime importance because the imbalance between apoptosis and cell proliferation determines the pathogenesis pathway of H .…”
Section: Discussionmentioning
confidence: 99%